2014
DOI: 10.1016/j.cell.2014.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Repair of a DNA-Protein Crosslink by Replication-Coupled Proteolysis

Abstract: Summary DNA-protein crosslinks (DPCs) are caused by environmental, endogenous, and chemotherapeutic agents and pose a severe threat to genome stability. We use Xenopus egg extracts to recapitulate DPC repair and show that this process is coupled to DNA replication. A DPC on the leading strand template arrests the replisome ahead of the lesion by stalling the CMG helicase. The DPC is then degraded on DNA, yielding a peptide-DNA adduct that is bypassed by CMG. The leading strand subsequently resumes synthesis, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
325
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(358 citation statements)
references
References 50 publications
30
325
2
1
Order By: Relevance
“…For example, yeast Wss1 protease cleaves the protein constituent of DPC at blocked replisomes (21). Furthermore, repair of a plasmid-embedded DPC in Xenopus egg extracts is coupled to DNA replication (22). We found that the DPC-induced replication block is removed if the protein constituent of DPC is digested to amino acids with proteinase K (Figs.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…For example, yeast Wss1 protease cleaves the protein constituent of DPC at blocked replisomes (21). Furthermore, repair of a plasmid-embedded DPC in Xenopus egg extracts is coupled to DNA replication (22). We found that the DPC-induced replication block is removed if the protein constituent of DPC is digested to amino acids with proteinase K (Figs.…”
mentioning
confidence: 81%
“…Covalent DPCs have been detected in peripheral blood lymphocytes from breast cancer patients undergoing treatment with cyclophosphamide. 4 Recent studies by Jentsch and co-workers (20,21) and Walter and co-workers (22) have provided evidence that DPCs are subject to proteolytic cleavage to the corresponding DNA-peptide lesions, which are subsequently removed from DNA in a replication-dependent repair process. Thus, it is critically important to investigate the activ-ity and accuracy of DNA polymerases on DNA-protein and DNA-peptide lesions.…”
mentioning
confidence: 99%
“…40 It is important to note that these proteases appear to leave a small peptide still crosslinked on DNA. 11,40 As in the case of ICLs and monoadducts, these peptides may still need to be removed via nucleolytic processes in order to complete DNA replication (Fig 9). Among possible structure-specific endonucleases that may process cross-linking adducts, loss of Swi9 or Swi10 alone led to significant sensitivity to acetaldehyde (Fig 4).…”
Section: Discussionmentioning
confidence: 99%
“…6 The Fanconi anemia (FA) pathway plays a critical role in the repair of ICLs, [7][8][9][10] although the role of this pathway in DPC repair has not yet been well understood. 11 Fanconi anemia is an inherited disease that is characterized by bone marrow failure and a strong predisposition to cancer. 12 At least 19 genes have been implicated in the FA pathway, 13 which is thought to coordinate at least 3 downstream repair processes; including homologous recombination (HR), nucleotide excision repair (NER), and translesion DNA synthesis (TLS).…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations have revealed that the ability of DNA polymerases to bypass DNA-peptide conjugates is dependent on the lesion size, the attachment site within the DNA, and polymerase identity (10,(21)(22)(23)(24)(25)(26)(27)(28)(29). Lloyd and co-workers (26) have reported that human polymerase (hpol) and its Escherichia coli orthologue pol IV were able to catalyze error-free primer extension past DNA templates containing tetra-and dodecapeptides conjugated to the N 2 position of guanine via a trimethylene linker.…”
Section: Dna-protein Cross-links (Dpcs)mentioning
confidence: 99%